3D NUMERICAL STUDY OF SURFACE ROUGHNESS ON CONVEX SURFACE TURBINE SAVONIUS FOR AERODYNAMIC PERFORMANCE IMPROVEMENT - Abhista, Nadhif Rayhan; Sakti, Gunawan; Wulansari, Ajeng (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
The purpose of this study is to improve efficiency by modifying the roughness of the Savonius turbine with the use of sandpaper on its convex surface. This research uses numerical methods using ANSYS software and Fluent CFD simulations with a 3D model of the Savonius wind turbine. The Savonius wind turbine used has a blade diameter of 100 mm, with variations in sandpaper surface roughness no 120, 180, and 320. The research used Reynolds Number Re = 6.34×104 with a speed of 5m/s. The results of this study Savonius turbine with surface roughness has not been able to improve the performance of the conventional Savonius turbine. The addition of variations has not obtained better results, both from the coefficient of moment experiencing a performance decrease of 0.83%, coefficient of power experiencing a performance of 12.8%, coefficient of drag increasing by 3.21% and coefficient of lift increasing by 3.11%.